A checklist of the Anopheles mosquito species (Diptera: Culicidae) in Bhutan - Rinzin Namgay (2018)
© 2018 Elsevier B.V. The present paper records, for the first time, the Anopheles fauna of Bhutan, determined from surveys conducted from 2007 to early 2018. Adult mosquitoes were collected mainly on cattle bait and occasionally in human landing catches. Collections of immature stages were performed in various aquatic habitats. Larvae were preserved or reared to adults. Identification was based on morphological characters using available keys. A total of 30 species were identified, including nine species of subgenus Anopheles and 21 species of subgenus Cellia. Distribution and collection data are provided with notes on the locations and habitats of the species. Anopheles pseudowillmori is suspected to be a vector of malarial parasites in the plains and hilly forested areas of the country because it is widely distributed and the most common species collected in human landing catches. Notes also include observed morphological variation observed in An. baileyi and An. lindesayi, which differ from the type forms. Corrections are made for previous reports of Anopheles in Bhutan. The need for further surveys and molecular identification of members of species complexes and morphological variants is emphasized.